Nursing Students’ Perception of Learning Environment in different Colleges of Pokhara - Gharti, Kamala; Gurung, Gaura; Maharjan, Neelam; Kunwar, Ranjan (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: The learning environment of nursing campuses is a significant factor in determining the success of nursing students' in achieving academic excellence and qualities of nursing care delivery. This study was aimed to assess the nursing students' perception of learning environment in different nursing colleges.Methods: The cross sectional institutional based study was carried out among bachelor level nursing students of selected nursing colleges of Pokhara from Jan 01 to 23/2022. The purposive sampling technique was used. The data was collected through a structured validated tool Dundee Ready Education Environment Measure (DREEM) inventory. Descriptive statistics (percentage, mean, SD) and inferential statistics one-way (ANOVA) at the level of 0.05% was used to find out the difference in the score of the perception of learning environment and subscales of DREEM across the selected demographic variables.Results: This study found that 85.4 % nursing students perceived their learning environment more positive than negative and only (1.5%) students' perceived excellent learning environment in their college. The significant differences was found between the years of enrolment for the overall perception of the learning environment and the five subscales of learning environment (p